Novel porous anatase TiO2 nanorods and their high lithium electroactivity - Li, Chang Ming (2013)
We demonstrated a simple approach for the synthesis of a kind of novel porous anatase TiO2 nanorods. The method is based on a reaction in composite-hydroxide eutectic system and normal atmosphere without using an organic dispersant or capping agent. The synthesis technique is cost effective, easy to control and is adaptable to mass production. This is the first time TiO2 nanorods with a porous structure are fabricated by using this method. The as-prepared material was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), nitrogen adsorption and desorption experiments and electrochemical measurements. The results showed that the anatase TiO2 nanorods obtained in our experiment have a large specific surface area with a porous structure which makes it have a potential application in catalysts and battery materials, especially in lithium ion batteries. In this study, we mainly tested their electrochemical performance as negative materials for lithium ion batteries. Further research to optimize synthesis conditions, particularly to develop their application in the field of catalysis is currently in progress.